Fokal epilepsili hastalarda depresyon ve anksiyete bozuklukları - (:unkn) unknown (My University, 2006)
Bilimsel zemin: Epilepsi hastalarında, depresyon ve anksiyete bozukluklarına normal popülasyona göre daha sık rastlanmaktadır. Farklı yayınlarda değişik sayılar belirtilmekle beraber, depresyon %10- 30, anksiyete bozukluğu % 15-25 oranında görülmektedir, ilaca dirençli olgularda oranlar daha da artmaktadır. Amaç: Bu çalışmada amaç, fokal epilepsi olan hastalarımızda depresyon ve anksiyete bozukluklarının oranlarını ortaya koymak ve bunların nöbet özellikleri, lezyon lokalizasyonu ve tedavi ile ilişkisini araştırmaktır. Gereç ve yöntemler: Fokal epilepsisi olan 94 hastada Hamilton depresyon değerlendirme ölçeği, Hamilton anksiyete değerlendirme ölçeği kullanıldı. Sonuçlar: Kontrol grubu ile karşılaştırıldığında, fokal epilepsisi olan hastalarımızda depresyona %23.4, anksiyete bozukluğuna %47.8 oranında rastlandı. Bu hastalarda depresyon ve anksiyete bozukluğunun nöbet başlangıç yaşı, nöbet süresi, lezyon lokalizasyonu veya almakta oldukları tedavi (mono veya politerapi) ile ilişkisinin olmadığı saptandı. Yorum: Fokal epilepsisi olan hastalarda depresyon ve anksiyete bozuklukları sık görülmektedir ve gerekli değerlendirmeler yapılarak erken evrede psikiyatrik destek verilmelidir.

Depression and Anxiety Disorders in Focal Epilepsy Patients Scientific background: Depression and anxiety disorders are more common in people with epilepsy than in the general population. Depression has been reported in 10-30%, and anxiety disorders in 15- 25% among epilepsy patients and these values can be changed in different studies. Futhermore they increase in drug resistance cases. Objectives: The aim of this study is to emphasize the depression and anxiety disorders among focal epilepsy patients in our clinic and search the relationship between depression-anxiety disorders and seizure features, lesion localization and medication treatments. Materials and methods: Ninety-four patients with focal epilepsy were included in the study. Hamilton depression scale and Hamilton anxiety inventory were used for evaluate depression and anxiety symptoms. Results: Depression was present in 23,4% and anxiety disorders in 47.8% in focal epilepsy patients when compared to control. There were no relationships between depression or anxiety and the duration of epilepsy, age of seizure onset, localization of lesion and the type of treatment (mono-poly therapy). Conclusion:Depression and anxiety disorders are common in focal epilepsy patients and psychiatric support has to be given at an early stage.
Depression and anxiety disorders in focal epilepsy patients
Keywords: Nörolojik Bilimler; Psikiyatri; Psikoloji